The Day Israel Attacked America | Special Series - Al Jazeera English (2014)
Al Jazeera investigates the shocking truth behind a deadly Israeli attack on a US naval vessel. In 1967, at the height of the Arab-Israeli Six-Day War, the Israeli Air Force launched an unprovoked attack on the USS Liberty, a US Navy spy ship that was monitoring the conflict from the safety of international waters in the Mediterranean. Israeli jet fighters hit the vessel with rockets, cannon fire and napalm, before three Israeli torpedo boats moved in to launch a second more devastating attack. Though she did not sink, the Liberty was badly damaged. Thirty-four US servicemen and civilian analysts were killed, another 171 were wounded. Later Israel apologised for what it claimed to be a tragic case of mistaken identity. It said that it had believed the ship to be hostile Egyptian naval vessel. US President Lyndon Johnson was privately furious but publicly the White House chose not to challenge the word of its closest Middle East ally and accepted that the attack had been a catastrophic accident. However, as this exclusive Al Jazeera investigation reveals, fresh evidence throws new light on exactly what happened that fateful day – and the remarkable cover up that followed. Subscribe to our channel: http://bit.ly/AJSubscribe Follow us on Twitter / ajenglish Find us on Facebook / aljazeera Check our website: http://www.aljazeera.com/ Check out our Instagram page: / aljazeeraenglish #US #Israel #USSLiberty #AljazeeraEnglish